Does the public haze pollution concern expressed on online platforms promoted pollution control? – Evidence from Chinese online platforms. (10th October 2021) - Wu, Wenqi; Wang, Wenwen; Zhang, Lu; Wang, Qiaoyu; Wang, Lujing; Zhang, Ming
Abstract: With the continuous deterioration of haze pollution and the increasing public awareness of environmental protection, more and more netizens are paying attention to the problem of haze pollution on online platforms, expressing environmental demands, supervising and accusing corporate pollution. Environmental concerns expressed by netizens on social media platforms exert strong public pressure on polluting enterprises with the popularity of smart phones. In this paper, a dynamic spatial econometric model is used to study the effects of network demand intensity on environmental pollution, taking into account the endogenous, regional differences and spatial spillover effects of explanatory variables. The total number of posts, likes, retweets, and comments on Weibo with the predefined search terms "haze" and the number of Baidu index comprised the public concern. Geographical detector model confirmed that the public's concern about haze pollution expressed on new media is closely related to haze condition. The results showed that new media network public opinion can alleviate haze pollution, but there are significant regional differences. From a regional point of view, the inhibition effect of new media network public opinion on haze pollution was the most significant in the central region, but it was not significant in the eastern and western regions. In addition, haze pollution showed obvious "cumulative effect" characteristics in the time dimension, and "spillover effect" characteristics in the space dimension.